2021
DOI: 10.3390/ani11113303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ambient Temperature on the Performance and Thermoregulatory Responses of Commercial and Crossbred (Brazilian Piau Purebred Sires × Commercial Dams) Growing-Finishing Pigs

Abstract: The study aimed at evaluating the effects of high ambient temperature (HT: 30 °C) on the thermoregulatory responses and performance of commercial and Piau crossbred (Brazilian Piau breed sires × commercial genotype dams) growing pigs. Commercial and Piau crossbred pigs were reared under thermoneutral (TN: 22 °C) or HT conditions during a 14-day experimental period. Feeding (daily) and animals (beginning and end) were weighted to obtain performance parameters. Skin and rectal temperatures, respiratory rate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Cuellar et al [ 42 ] reported lower average T V and significantly lower Max Tv in crossbred animals (mostly Brown Swiss × Holstein F1 animals) compared to Holstein and Brown Swiss individuals . Similar results were found in sheep [ 43 ] and pigs [ 44 ]. These findings suggest that the effects of breed or line on CR should be further investigated in future studies.…”
Section: Resultssupporting
confidence: 88%
“…Cuellar et al [ 42 ] reported lower average T V and significantly lower Max Tv in crossbred animals (mostly Brown Swiss × Holstein F1 animals) compared to Holstein and Brown Swiss individuals . Similar results were found in sheep [ 43 ] and pigs [ 44 ]. These findings suggest that the effects of breed or line on CR should be further investigated in future studies.…”
Section: Resultssupporting
confidence: 88%
“…In the context of the surface temperature of animals, kriging maps can be applied to estimate the spatial distribution of surface temperatures over the skin. The values estimated by kriging were similar to those found through the measurements of the authors of [39], obtained using infrared thermography in pigs, who found values ranging from 32 to 34 °C, similar to the values recorded for the animals in the AEC and FV treatments at 08:00 h in the morning. The authors of [39] also found temperature values in the caudal-dorsal region ranging from 35.8 to 37.7 °C, which were similar to the values found in this study for the animals at 12:00 h, validating the results of the kriging.…”
Section: Discussionsupporting
confidence: 88%
“…The animals' body temperature was checked by means of thermal images obtained with a Flir i60 thermal imager. For thermal image registration, the camera angle was standardized, and the distance between the equipment and the animal was maintained at 1 m, as in [39,40]. The camera emissivity was set to 0.98, which is suitable for biological tissues [41], for image correction using Flir software, version 1.9.…”
Section: Physiological Variables Of the Animalsmentioning
confidence: 99%
“…The authors recommend that pigs be delivered two weeks before the start of the experiment for successful acclimatization so that the pigs become accustomed to the food and environment. [18, 19]…”
Section: Discussionmentioning
confidence: 99%